Evaluation of stress tolerant indices and yield of barley landraces under drought condition - Shrestha, Abhisek; Thapa, Bharti; Marahatta, Santosh; Dhakal, Krishna Hari; Gauchan, Dhurva Prasad; Yadav, Tirth Narayan (Journal of Agriculture and Natural Resources, 2025)
Barley landraces serve as important genetic resources for enhancing drought tolerance in crop development programs. This study aimed to assess drought tolerance genotype among fourteen barley landraces using CRD replicated thrice, under controlled poly-house conditions at College of Natural Resource Management (CNRM), Bardibas, Nepal. Plants were exposed to water-deficit stress (60 centibars for 7 days) at the crown root initiation, tillering, and grain filling stages, while controls were maintained under optimal moisture. Physiological traits (chlorophyll content, flowering and maturity duration) and yield components were recorded, and drought tolerance indices (STI, MP, GMP, SSI, TOL, YSI) were computed. Significant genotypic variation was observed for drought response. Landrace AFU 202501 exhibited moderate growth reduction (9.2%) and high chlorophyll retention (93.2% of control), indicating sustenance under water-deficit condition with stable yield. Saptari Local demonstrated early maturity with minimal yield reduction (TOL = 0.86; SSI = –0.068) as a drought-escape mechanism, whereas NGRC 6010 was highly sensitive with severe growth inhibition. Based on stress indices, AFU 202501 and Gaushala Local depicts high-yielding potentiality under both stress and non-stress conditions (STI > 1.3), while Saptari Local exhibited superior yield stability (YSI = 0.943). The finding suggests chlorophyll retention and phenological plasticity as reliable indicators of drought adaptation, and identify AFU 202501 and Saptari Local as promising parental lines for breeding drought-tolerant barley, warranting further validation under multi-environment field conditions.